Lasers in maxillofacial surgery - Review of literature - Khadar Vali Shaik; Mohammed Ibrahim Nazal Alanazi; Rakan Menwer Albilasi; Bader Falah Arqoub Albalawi; Faris Alturqi Alruwaili (Wolters Kluwer Medknow Publications, 2021)
The availability of different wavelengths of lasers has created a surgical panacea in the last decade and laser technology has become the standard of care for many oral and maxillofacial surgical procedures. In this article, based on literature search, we have reviewed the usage of laser in maxillofacial surgery based on the current evidence available on laser-assisted maxillofacial surgery, in PubMed database.